A Theoretical Approach to Inclusion Complexation of Benzanilide and Fast Violet B with \(β\)-cyclodextrin - Prabhu, A. Antony Muthu (Challenges and Advances in Chemical Science Vol. 2, 2021)
The theoretical investigation of inclusion complexation of amide-imidol tautomer of two guest molecules benzanilide (BA) and fast violet B (FVB) with \(β\)-cyclodextrin (\(β\)-CD) using DFT B3LYP 3-21G method in the gas phase. Benzanilide has no substitution in the basic skeleton and the other selected compound substituted with three groups such as –NH2, -CH3 and –OCH3 group in the same aromatic ring. The tautomer of two selected compounds was formed the stable inclusion complexes with the \(β\)-CD supramolecule. The theoretically calculated complexation energy was observed the negative value for all the inclusion complexes. This method was applicable to determine the structural assignment of the inclusion complexes between BA, FVB and \(β\)-CD.